Pengaruh Antara Motivasi, Tingkat Pendidikan Orang Tua terhadap Hasil Belajar Peserta Didik pada Program Pendidikan Paket C di SKBN Surabaya - Ramadhan, Aditya Ilham; Soedjarwo, Soedjarwo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
The purpose of this study was to analyze the influence between the level of parental education and the learning motivation of students in the package C program at SPNF SKB Surabaya. more in-depth knowledge and understanding of the importance of students' parents having an adequate level of education, because indirectly this will support their children's learning motivation as students at school. Therefore, the results of this study will also make us more aware, especially the parents of students that an adequate level of education is a very important factor and can influence student learning motivation. This research uses a type of quantitative approach research with descriptive writing methods. The data collection technique in this study is by using the learning motivation questionnaire method, and documenting report cards. The results of this study were tested for data analysis by using a linear regression test between learning motivation and learning outcomes. So it can be concluded that the results of this study are learning motivation has a significant effect on the learning outcomes of learning citizens. This is indicated by a significant value of 0.017 which is smaller than the value of ? (0.05). While the level of education of parents does not significantly influence the learning outcomes of the learning community. This is indicated by a significant value of 0.416 which is greater than the value of ? (0.05). Taken together learning motivation and parents' education level significantly influence learning outcomes with a significance value of 0.049 less than 0.05.